Field notes and Pam Allen and Reid I. Allen letter to Thomas H. Kent, December 2, 1991 - Allen, Pamet al; Allen, Reid I.et al (1991)
List of birds and locations contributed by Pam Allen and Reid I. Allen with observers Sam Dunkle, Francis L. Moore, Bery Engebretsen, Robert K. Myers and others. Included with the field notes is a letter from Pam Allen and Reid I. Allen to Thomas H. Kent regarding fall birding. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1991. Epson - sheet feed